Accurate calculations of beyond-Voigt line-shape parameters from first principles for the He-perturbed HD rovibrational lines: A comprehensive dataset in the HITRAN DPL format. (December 2021) - Stankiewicz, Kamil; Stolarczyk, Nikodem; Jóźwiak, Hubert; Thibault, Franck; Wcisło, Piotr
Highlights: Comprehensive dataset of beyond-Voigt line-shape parameters for He-perturbed HD. Ab initio quantum scattering calculations of generalized spectroscopic cross-sections. Ab initio investigation of pressure broadening, shift and Dicke parameters. Data for all electric dipole and quadrupole lines that are present in HITRAN database. Abstract: We report a comprehensive dataset of beyond-Voigt line-shape parameters (pressure broadening and shift coefficients, their speed-dependences, and the complex Dicke parameters) for all electric dipole and quadrupole transitions within the ground electronic state in He-perturbed HD that are present in the HITRAN database. The parameters are determined from generalized spectroscopic cross-sections which we obtain by solving ab initio quantum scattering problem using the close-coupling formulation and the state-of-the-art potential energy surface of the HD-He interaction. We parametrize the temperature dependence of the line-shape parameters with double-power-law representation (DPL), recommended for the HITRAN database. Comparison with the analogous results for the H 2 -He system reveals a strong isotopologue dependence.